2017
DOI: 10.1177/0954410017690549
|View full text |Cite
|
Sign up to set email alerts
|

Multi-point optimization of transonic airfoils using an enhanced genetic algorithm

Abstract: In this study, two new techniques are proposed for accelerating the multi-point optimization of an airfoil shape by genetic algorithms. In such multi-point evolutionary optimization, the objective function has to be evaluated several times more than a single-point optimization. Thus, excessive computational time is crucial in these problems particularly, when computational fluid dynamics is used for fitness function evaluation. Two new techniques of preadaptive range operator and adaptive mutation rate are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The blade shape has 56 design parameters, with a population size of 64 and a generation size of 100 are utilized. However, Timnak, N. et al 33 applied the GA method for the optimum design of a transonic airfoil, the PARSEC method with nine design variables was applied for airfoil parameterization. The total population of each generation is set to be 20.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…The blade shape has 56 design parameters, with a population size of 64 and a generation size of 100 are utilized. However, Timnak, N. et al 33 applied the GA method for the optimum design of a transonic airfoil, the PARSEC method with nine design variables was applied for airfoil parameterization. The total population of each generation is set to be 20.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Timnak and Jahangirian (2018) conducted research on the use of genetic algorithms and PARSEC parameterization for airfoil optimization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Trigonometric surfaces over triangles with modifiable form parameters can be produced using this approach [5]. They investigated the use of genetic algorithms and PARSEC parameterization for airfoil optimization [6]. A control point is defined, using point clouds of the airfoil [7].…”
Section: Introductionmentioning
confidence: 99%
“…is has been applied to optimize the performance of a transonic airfoil [12]. Jin et al [13] extensively reviewed the various surrogate models using their prediction accuracy, efficiency, and robustness and concluded that for higher-order nonlinear problems, neural networks should be used.…”
Section: Introductionmentioning
confidence: 99%